Level of Adoption and Perception of Farmers on Phosphorus Based Fertilizers for Cowpea Production in Katsina State, Nigeria - Hussaini Yusuf Ibrahim; Umar Ibrahim; Abdullahi Abubakar Khidir; Abdullahi Sani (مجلة ديالى للعلوم الزراعية, 2023)
The study analyzed farmers' level of adoption and perception of phosphorus based fertilizers for cowpea production in Katsina state, Nigeria. A total of 153 cowpea farmers were sampled using a multi-stage sampling technique. Primary data was utilized in the study. The data was collected using a structured questionnaire by trained enumerators. Descriptive statistics, Kendalls’ coefficient of concordance and acceptability index were employed for data analysis. The results showed that the mean age for cowpea farmers was 41 years. Distribution of the respondents by gender reveals that 85.6% were males and the remaining 14.4% were females. The result of farmers’ perception of phosphorus-based fertilizer used shows a moderate agreement of 0.30 which indicates different perceptions among respondents. The study further revealed that the acceptability index of 6.54% was very alarming because cowpea farmers committed a small portion of their farmland toward adopting the technology. The level of knowledge of the cowpea farmers on phosphorus based fertilizers was very low, leading to a very low level of acceptance of phosphorus fertilizers in the study area. It was recommended that be made available and affordable to the cowpea farmers as this will increase the rate of technology adoption in the study area.